In Utero Antidepressant Exposure and Neurodevelopment in Preterm Infants - Batton, Beau; Batton, Emily; Weigler, Kara; Aylward, Glen; Batton, Daniel (American Journal of Perinatology, 2013)
Objective To investigate the impact of in utero selective serotonin reuptake inhibitor (SSRI) exposure on neurodevelopment in a cohort of preterm infants.Study Design Retrospective case control study of preterm infants ≤366/7 weeks gestation with in utero SSRI exposure. Subjects were matched to controls by gestational age, year of birth, birth weight, gender, and age at neurodevelopmental assessment. Neurodevelopment was assessed with the Bayley Infant Neurodevelopmental Screener and the Bayley Scales of Infant Development.Results The 19 infants with in utero SSRI exposure were similar to controls in demographic data, birth weight, and in-hospital morbidity. The mean ± standard deviation (SD) Mental Developmental Index score for study infants at 36 months was 94 ± 15 versus 91 ± 10 for controls (p = 0.46). The mean ± SD Psychomotor Developmental Index score was also similar between groups: 79 ± 21 for study infants versus 75 ± 20 for control infants (p = 0.72). Other neurodevelopmental outcomes were comparable.Conclusion In this cohort of preterm infants, in utero SSRI exposure was not associated with adverse neurodevelopment above the baseline risk for this degree of prematurity. Larger studies are needed to obviate the risk of a type II error.
Keywords: pregnancy; selective serotonin reuptake inhibitor; preterm infant; neurodevelopment